2018
DOI: 10.1007/s12274-018-2174-x
|View full text |Cite
|
Sign up to set email alerts
|

Photo-controlled release of paclitaxel and model drugs from RNA pyramids

Abstract: Stimuli-responsive release of drugs from a nanocarrier in spatial-, temporal-, and dosage-controlled fashions is of great interest in the pharmaceutical industry. Paclitaxel is one of the most effective and popular chemotherapeutic drugs against a number of cancers such as metastatic or nonmetastatic breast cancer, non–small cell lung cancer, refractory ovarian cancer, AIDS-related Kaposi’s sarcoma, and head and neck cancers. Here, by taking the advantage of RNA nanotechnology in biomedical and material scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…169 These pyramids were functionalized with the chemotherapeutic drug paclitaxel via photocleavable spacers, and irradiation with ultraviolet light induced drug release and cytotoxicity in MDA-MB-231 breast cancer cells. 169 In a different example, Li et al reported the self-assembly of a nuclease-resistant, 2 0 -deoxyfluoro U/C modified RNA tetrahedron based on the phi29 pRNA 3WJ (Fig. 5G).…”
Section: Drug Deliverymentioning
confidence: 99%
“…169 These pyramids were functionalized with the chemotherapeutic drug paclitaxel via photocleavable spacers, and irradiation with ultraviolet light induced drug release and cytotoxicity in MDA-MB-231 breast cancer cells. 169 In a different example, Li et al reported the self-assembly of a nuclease-resistant, 2 0 -deoxyfluoro U/C modified RNA tetrahedron based on the phi29 pRNA 3WJ (Fig. 5G).…”
Section: Drug Deliverymentioning
confidence: 99%
“…Similar approaches have been reported for PDT, wherein PDT is combined with chemotherapy using nanoparticles containing ROS sensitive linked drugs. The most commonly used ROS sensitive linker is the thioketal moiety, which in the presence of ROS can degrade releasing an attached drug to the cell environment . A more interesting approach is the example of micelles formed by an amphiphilic block polymer, composed of PEG and a selenium containing nylon derivative .…”
Section: Drug Deliverymentioning
confidence: 99%
“…It presented a large number of gaps, obviously different from Figure I (a), (b) and (c), which providing a channel for the release of pesticides. [7][8][9][10] Figure IV gave the pesticide film releases pesticide under light control conditions. Multi-pulsatile pesticide release could be achieved by the photo-responsive controlled pesticide release film through UV and visible light irradiation, and approximately 45 % of the loaded acetamiprid was released.…”
Section: Photo-responsive Property Of Peg Supported Spiropyran Carmentioning
confidence: 99%
“…Photo-responsive drug release systems are environment-friendly and efficient for drug delivery applications, which can initiate release of the encapsulated drug only at controllable rate, at needed time, and at the suitable site, and have been increasingly investigated, especially in medicine, for the treatment of cancer. [4][5][6][7] At present, few studies have been done on the photoresponsive controlled release of pesticides. Ding et al synthesized photoresponsive polymeric propesticide micelles based on photolabile o-nitrobenzyl group for a controlled release of the herbicide dichlorophenoxyacetic acid (2,4-D).…”
Section: Introductionmentioning
confidence: 99%